Bioequivalence study of two perindopril erbumine tablet formulations in healthy volunteers - Setiawati, Effi; Deniati, Siti Hawa; Yunaidi, Danang Agung; Handayani, Lucia Rat; Santoso, Iwan Dwi; Arland, Joan Aprilla; Setiawati, Arini; Lian, Lai Yeo (Arzneimittelforschung, 2011)
The present study was performed to compare the bioavailability of two perindopril erbumine (CAS 107133-36-8) 4 mg tablet formulations (test formulation and reference formulation). This study was a randomized, single-blind, two-period, two-sequence cross-over study which included 20 healthy adult male and female subjects under fasting conditions. In this study, one subject withdrew from the study and one reserve subject did not appear at both periods. The pharmacokinetic parameters were assessed based on the concentrations of perindopril (CAS 82834-16-0) and perindoprilat (CAS 95153-31-4) because perindopril has litte pharmacologic activity until hydrolized in the liver into its active metabolite, perindoprilat. The blood samples from 18 subjects were analyzed for plasma concentrations of perindopril and perindoprilat. In each of the two study periods (separated by a washout of three weeks) a single dose of test or reference drug was administered.Plasma concentrations of the drug were determined by LC-MS/MS method.The pharmacokinetic parameters assessed in this study were area under the plasma concentration-time curve from time zero to 192 h (AUCt), area under the plasma concentration-time curve from time zero to infinity (AUCint), the peak plasma concentration of the drug (Cmax), time needed to achieve the peak plasma concentration (tmax), and the elimination half-life (t1/2).The geometric mean ratios (90% CI) of the test drug/reference drug for perindopril and perindoprilat were 106.59% (92.97–122.20%) and 100.56% (94.11–107.46%) for AUC,, 106.64% (93.39–121.77%) and 100.88% (95.30–106.80%) for AUCint, and 101.23% (87.39–117.27%) and 99.30% (90.42–109.05%) for Cmax( respectively. The 90% confidence intervals calculated for AUCt and Cmax of perindopril and perindoprilat were within the standard bioequivalence range (80–125% for AUC and Cmax). It was concluded that the two perindopril erbumine tablets (test and reference drug) were bioequivalent in terms of the rate and extent of absorption.
Keywords: Angiotensin converting enzyme (ACE) inhibitor; Perindopril; Perindopril erbumine, bioavailability, bioequivalence, pharmacokinetics; Perindoprilat; Provinace